MENTORING PAYMENT SYSTEM ADMINISTRATION COURSE LEARNING INSTITUTIONS IN BSC USING VISUAL BASIC 6.0 - Bolivia Dwi Agustiani; Ire Puspa Wardhani, SKom, MMSI (Jurnal Sistem Informasi, 2004)
It contains scientific writing about Tutoring payment administration information, because there are no computer tool, which handles the administration of payments often have difficulties, including: length of student records data, transaction data are not neatly arranged.Under these circumstances, the writer makes reference to the proposed system with current procedures. This system is expected to help overcomeexisting problems in order to improve efficiency, effectiveness and productivity and quality of care.